Blended Learning in English Language Learning in Post Pandemic Era: Literature Review - Putri Indah Pratiwi; Sri Sumarni (English Language and Literature International Conference (ELLiC) Proceedings, 2023)
In the post-pandemic era, several teaching methods are advised to be employed to address some of the issues English as a second language/English as a foreign language learners confront challenges. this paper aims at present geographical distribution and the effectiveness of blended learning. The method of this study was a literature review, This study chose a total of 32 publications published between 2019 and 2023. The result shows instructors and students in various English as second language/English as a foreign language situation had a favourable reaction to blended learning. Since this teaching technique created the road and provided a new avenue for English language practice in an ESL/EFL setting, blended learning has also been underlined by many academics as being applied in English teaching and learning. Finally, it is advised to implement this strategy as an optional language learning model in the post-pandemic era.